2010
DOI: 10.1111/j.1540-8159.2010.02801.x
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical and Experimental Analysis of Radiofrequency Ablation with a Multielectrode, Phased, Duty-Cycled System

Abstract: Both the in vitro and computational model results demonstrate that lesion depth decreases consistently as the bipolar-to-unipolar ratio increases-suggesting a clinical application to potentially control lesion depth with higher fidelity than is currently available. The effect of variable design parameters and clinical conditions on RF ablation can now be expeditiously studied with this validated model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…First, at temperatures below 100ºC,  increases. However, there are discrepancies about the rate of this increase, from +1.5%/ºC [15] to +2%/ºC [8], and about the increase type, linear [16,17] or exponential [13,18]. 5 At temperatures above 100ºC vaporization occurs and desiccation implies a rapid drop of .…”
Section: Temperature-dependence Of Electrical Conductivity (mentioning
confidence: 99%
See 1 more Smart Citation
“…First, at temperatures below 100ºC,  increases. However, there are discrepancies about the rate of this increase, from +1.5%/ºC [15] to +2%/ºC [8], and about the increase type, linear [16,17] or exponential [13,18]. 5 At temperatures above 100ºC vaporization occurs and desiccation implies a rapid drop of .…”
Section: Temperature-dependence Of Electrical Conductivity (mentioning
confidence: 99%
“…Most RFA theoretical models have used a constant value for k [14,15,17,[20][21][22], probably due to the fact that changes in k with temperature are not so marked as in  [10,23].…”
Section: Temperature-dependence Of Thermal Conductivity (K)mentioning
confidence: 99%
“…The 2:1 setting gives more energy in unipolar mode which creates deeper lesions but with the possible risk of gaps between the poles. Several studies have reported a gradual increase in lesion depth by increasing the ratio of unipolar energy delivered by the PVAC [11][12]. Wijffels et al [11] reported that all energy setting (unipolar, 1:1, 2:1 and 4:1 bipolar/unipolar ratio) produces transmural lesions.…”
Section: Discussionmentioning
confidence: 99%
“…The energy can be delivered in a unipolar or bipolar setting or combined in various ratios. A higher proportion of unipolar energy will give deeper lesions but less energy between the poles possibly leading to non-continuous lines [12]. Although certain energy settings have been recommended for PV isolation there are no randomized…”
Section: Introductionmentioning
confidence: 99%
“…1. An advanced balloon catheter design with multiple sensors on the outside surface was reported for enabling the catheter to obtain temperature, flow characteristics, tactile, optical, and electrophysiological data from the tissue-balloon interface [17][18][19][20][21][22][23][24][25][26][27][28]. While the CA is considered as one of the best methods for diagnosing and treating AF, there is a higher risk of procedural complications due to the complexity of technique and the location of ablation sites [5].…”
Section: Introductionmentioning
confidence: 99%